The Johannine footwashing as the sign of perfect love: an exegetical study of John 13:1-20 - Mathew, Bincy (Wissenschaftliche Untersuchungen zum Neuen Testament, 2018)
Cover -- Titel -- Acknowledgements -- Table of Contents -- Abbreviations -- General Introduction -- Chapter 1: The Footwashing: A Status Quaestionis -- A) The Footwashing: Non-Sacramental Interpretations -- I. The Footwashing as the Salvific Death of Jesus -- 1. Alan Culpepper (1991) -- 2. Marianne M. Thompson (2003) -- II. The Footwashing as the Vicarious or Atoning Death of Jesus -- 1. David Gibson (2007) -- 2. Otfried Hofius (2009) -- 3. Mark Matson (2014) -- B) The Footwashing: Sacramental Interpretations -- I. Francis J. Moloney (1991) -- II. Christopher Thomas (1991) -- C) Conclusion -- Chapter 2: "Except for the feet" John 13:10: A Text-Critical Analysis -- A) Variant Readings of John 13:10 -- B) External Criticism -- C) Internal Criticism -- I. Transcriptional Probability -- 1. Long Reading: The More Difficult Reading -- a) Are λούω and νίπτω Synonyms? -- (i) Leviticus 15:11 -- (ii) Tobit 7:9 -- (iii) Philo, De somniis -- (iv) Testament of Levi 9:11-12 -- (v) Aramaic Levi Document 19-25b -- (vi) Papyri Oxyrhynchus 840 -- (vii) Archaeological Evidence -- 2. The Long Reading Easily Explains Other Variations -- II. Intrinsic Probability -- 1. The Johannine Use of λούω and νίπτω -- 2. The Long Reading: A Grammatical Consideration -- D) Conclusion -- Chapter 3: "Ah, Yes! to Generous Souls How Noble Every Task!": Footwashing in the Ancient Jewish, Greek, and Roman Literature -- A) Previous Research on John 13 in Relation to Ancient Footwashing -- B) Footwashing in the Jewish Culture -- I. Washing One's Own Feet -- 1. Hygiene, Comfort and Hospitality -- a) Genesis 19:2 -- b) Genesis 24:32 -- c) Genesis 43:24 -- d) Judges 19:21 -- e) 2 Samuel 11:8 -- f) Canticles 5:3 -- 2. Ritual Setting -- II. Washing Someone Else's Feet -- 1. An Expression of Hospitality -- a) Genesis 18:4 -- b) Testament of Abraham -- c) 1 Timothy 5:10